On the Nature of Bridging Metal Atoms in Intermetalloid Clusters: Synthesis and Structure of the Metal‐Atom‐Bridged Zintl Clusters [Sn(Ge9)2]4− and [Zn(Ge9)2)]6−. Issue 39 (18th August 2016) - Bentlohner, Manuel M.; Jantke, Laura‐Alice; Henneberger, Thomas; Fischer, Christina; Mayer, Kerstin; Klein, Wilhelm; Fässler, Thomas F.
Abstract: The addition of Sn and Zn ions to [Ge9 ] clusters by reaction of [Ge9 ] 4− with SnPh2 Cl2, ZnCp*2 (Cp*=pentamethylcyclopentadienyl), or Zn2 [HC(Ph2 P=NPh)2 ]2 is reported. The resulting Sn‐ and Zn‐bridged clusters [(Ge9 )M(Ge9 )] q − (M=Sn, q =4; M=Zn, q =6) display various coordination modes. The M atoms that coordinate to the open square of a C 4 v ‐symmetric [Ge9 ] cluster form strong covalent multicenter M−Ge bonds, in contrast to the M atoms coordinating to triangular cluster faces. Molecular orbital analyses show that the M atoms of the Ge9 M fragments coordinate to a second [Ge9 ] cluster with similar orbitals but in different ways. The [Ge9 Sn] 2− unit donates two electrons to the triangular face of a second [Ge9 ] 2− cluster with D 3 h symmetry, whereas [Ge9 Zn] 2− acts as an electron acceptor when interacting with the triangular face of a D 3 h ‐symmetric [Ge9 ] 4− unit. Abstract : Electronically flexible Zintl clusters : Two possibilities to build up intermetalloid clusters based on Lewis acid/Lewis base concepts are shown for the intermetalloid clusters [Sn(Ge9 )2 ] 4− and [Zn(Ge9 )2 )] 6− . Sn and Zn atoms add to a nido Ge9 cluster to form a closo cluster. The Sn and Zn heteroatoms can then act as an electron donor and electron acceptor, respectively, towards a second Ge9 cluster (see figure).